The Role of Social Media and Participatory E-Democracy Practices in Palestine during COVID- 19 Pandemic in Good Governance - Niaz Daifallah (International Journal of Social Communication, 2024)
This article is an academic analysis contribution, that aims at focusing on the optimistic roles of social media in society, starting from the understanding of the sociality of social media from the point of view of the social theory, and applying the case of the study “The Participatory E-Democracy Practices in Palestine by the Government, the Citizens, and the Journalists on Social Media during COVID- 19 Pandemic Crisis Management, and the Fundamentals of Good Governance” to the theories of e-democracy and participatory democracy as a socio-political framework, also to examine the online communicational practices and interactions of both the governmental body and the citizens through social media platforms, in addition, to check to which extent they follow and take in consideration the participatory e-democracy and good governance fundamentals in the context of raising the values of the democratic culture in Palestine. On the other hand, the article highlights the pessimism side of social media from the point of view of the critical and digital surveillance media theories, as sub-topics in the contexts of online capitalism and the authoritarian logic of digital communication.